ANALYSIS ANALYSIS OF THE ITEMS IN THE SCIENCE SEMESTER EXAM AT SMP NEGERI 30 SOLOK SELATAN ACADEMIC YEAR 2019/2020 - Winda Pitri Lusi; Firda Az Zahra (Department of Science Education, 2022)
The Class VII Science Odd Semester Exam Questions at SMP Negeri 30 Solok Selatan for the 2019/2020 academic year are not analyzed qualitatively and quantitatively and do not have standardized questions. Standardized questions are questions that have been tried several times, have a coefficient of validity, reliability, level of difficulty, distinguishing power, and other information deemed necessary. Therefore, the researcher felt the need to analyze the items. This study aims to determine the quality of the items qualitatively and quantitatively (reliability, validity, distinguishing power, difficulty level, and distractor quality).This research is descriptive research. The research population consisted of all the answer sheets for the Class VII IPA odd semester examination at SMP Negeri 30 Solok Selatan for the academic year 2019/2020, totaling 26 students. The sampling technique used total sampling technique. The research instrument used a question construction quality questionnaire. Data collection techniques with document study. The quantitative results were analyzed using the ANATES program.Based on the research results, it was found that: 1) The construct validity of the questions did not yet fulfill all aspects, both in terms of science content, construction, and language; 2) The validity of the questions was low, dominated by invalid questions; 3) Reliability category is sufficient; 4) Poor differentiation; 5) Medium level of difficulty; 6) Distractor quality is good and functioning. Thus, the questions have not met the criteria for good and standardized questions, so they need to be revised.